Comparison of % composition of essential oil from peels and leaves of kaffir lime (Citrus hystrix) using hydrodistillation and solvent (ethyl acetate) extraction / Megawati Mohd Yunus - Mohd Yunus, Megawati (Faculty of Applied Sciences, 2009)
Essential oil from peels and leaves of kaffir lime were extracted by using hydrodistillation and solvent (ethyl acetate) extraction. Composition of essential oils were analysed by GC-Mass spectrometry. The major components of the hydrodistillated essential oils from peels of kaffir lime were limonene (16.85%) and cironellal (3.57%) whereas citronellal (2.80%), limonene (0.31%), and pinene (0.13%) were major components of essential oil of the ethyl acetate extract. The major component of the ethyl acetate extract from leaves of kaffir lime was citronellal (73.08%) and that from hydrodistillation was also citronellal (100%)